Evaluation of the Curriculum for the Untirta Electrical Engineering Vocational Education Study Program Referring to the Needs of the World of Work and the Industrial World - Ilham Akbar Darmawan; Ihsan Faturrohman (Politeknik Piksi Ganesha Indonesia, 2024)
This research aims to review and improve the curriculum of the Electrical Engineering Education Department at Sultan Ageng Tirtayasa University in accordance with developments in science and technology and the needs of stakeholders. Curriculum review and development is carried out by referring to graduate competencies in accordance with the Indonesian National Qualifications Framework (KKNI) in the field of Electrical Engineering and Electrical Engineering Education. This research is an evaluation research on curriculum implementation using the TIPP (Context, Input, Process, Product) model, and curriculum development through content analysis and discussion. The research results show that in general the implementation of the 2019 curriculum for the Vocational Education Department in Electrical Engineering is classified as appropriate (good) according to lecturer/alumni respondents, and quite appropriate (fairly good) according to student respondents. There are quite a lot of deficiencies, both in the content of the curriculum and the implementation of the curriculum, especially in the Input, Process and Product aspects. Based on the study of the evaluation results of the implementation of the curriculum and KKNI as well as the vision & mission and objectives of the Vocational Education Department of Electrical Engineering FKIP Untirta, a competency design can be formulated which should be mastered by undergraduate graduates majoring in Electrical Engineering Education as well as the draft curriculum framework. This design needs to be studied further and validated adequately so that a curriculum device can be produced that has relevance, quality and adequate benefits for students/graduates, society and the world of work.